An Insight into Cancer Cells and Disease Progression Through the Lens of Mathematical Modeling - Polychronis Michalakis; Dimitra Vasilaki; Ali Jihad Abdallah; Charilaos Asikis; Athina Niakou; Athanasios Stratos; Alexandros Tsouknidas; Elaine Johnstone; Konstantinos Michalakis (Current Issues in Molecular Biology)
During cancer initiation, normal cells acquire mutations disrupting standard cellular processes, activating oncogenes and inactivating tumor suppressor genes, acquiring the well-described hallmarks of cancer on the path to malignancy. This process is influenced by a combination of physiological and metabolic pathways, as well as environmental cues, and leads to abnormal cell cycle, increased cell motility, and invasive characteristics. Cancer cell organelles also present some distinct differences from those of normal cells. Cancer progression requires certain tumorigenic biochemical pathways to be activated. However, mechanical cues are also important, as they have an effect on cell differentiation and fate. A continuous biochemical–biomechanical interaction exists, which affects the mechanical properties of the cells, as well as their behavior. This review aims to focus on the mathematical relationships governing cancer mechanobiology and examine how the altered mechanical properties of a cancer cell may affect malignant progression.